2019
DOI: 10.1016/j.neo.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

SMAR1 favors immunosurveillance of cancer cells by modulating calnexin and MHC I expression

Abstract: Down-regulation or loss of MHC class I expression is a major mechanism used by cancer cells to evade immunosurveillance and increase their oncogenic potential. MHC I mediated antigen presentation is a complex regulatory process, controlled by antigen processing machinery (APM) dictating immune response. Transcriptional regulation of the APM that can modulate gene expression profile and their correlation to MHC I mediated antigen presentation in cancer cells remain enigmatic. Here, we reveal that Scaffold/Matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Decrease in MHC expression is also evident in cancer cells, which is a mechanism by which they evade the immune response by epigenetically modifying calnexin promoter. But infection with influenza virus in these cancer cells results in enhanced MHC-I presentation due to the increased expression of chromatin remodeling proteins, which stabilizes p53 expression and hence augments the immune surveillance of cancer cells (79). Therefore, molecules that can upregulate chromatin regulators and increase the MHC-I expression could potentially be used for COVID-19.…”
Section: Antigen Presentationmentioning
confidence: 99%
“…Decrease in MHC expression is also evident in cancer cells, which is a mechanism by which they evade the immune response by epigenetically modifying calnexin promoter. But infection with influenza virus in these cancer cells results in enhanced MHC-I presentation due to the increased expression of chromatin remodeling proteins, which stabilizes p53 expression and hence augments the immune surveillance of cancer cells (79). Therefore, molecules that can upregulate chromatin regulators and increase the MHC-I expression could potentially be used for COVID-19.…”
Section: Antigen Presentationmentioning
confidence: 99%
“…Studies have also revealed that high calnexin expression can promote tumor proliferation and growth in lung cancer ( 113 , 114 ). In both in vitro and an in vivo melanoma models, Scaffold/Matrix- Associated Region-1 (SMAR1) is directly involved in immune evasion mechanisms by positively regulating MHC-I expression through the downregulation of calnexin ( 115 ). Calnexin gene expression was found to be suppressed by the formation of a repression complex that binds to the matrix attachment region (MAR) site on the calnexin promoter.…”
Section: Therapeutic Strategies To Enhance Mhc-i Expressionmentioning
confidence: 99%
“…The upregulation of calnexin has been associated with a worse prognosis in several types of cancer, but results are still controversial. Although its increased expression was shown to negatively regulate tumor MHC I surface expression and promote STAT3 oncogene activation leading to tumor malignancy [ 45 , 46 ], calnexin expression levels were significantly higher only in Stage I lung cancer patients when compared to healthy controls, while in colorectal cancer (CRC), no associations were found between higher expressions of calnexin in CRC Stages II or III compared to normal tissue samples [ 47 , 48 ]. Additionally, low or defective expression of calnexin in primary breast cancer was reported to be associated with a higher risk of brain metastases, due to defects in T-cell-based immunosurveillance [ 49 ].…”
Section: Discussionmentioning
confidence: 99%